Controlling factors and mapping of linear erosive features in Santa Maria river watershed –RS - Petsch, Carina; Volpato Sccoti, Anderson Augusto; Souza Robaina, Luís Eduardo de; Trentin, Romario (Revista Brasileira de Geomorfologia, 2022)
Water erosion is one of the main causes of soil degradation and linear erosion mapping is one of the essential tools for its monitoring. In light of this, the goal from this research is to map the linear erosive features (LEF) of the Santa Maria River Basin (BHRSM), southwest region of RS, and understand which environmental factors are controlling or triggering erosion. In western RS there is a considerable concern associated with erosive processes that occupy large extensions and cause changes in the dynamics of use and changes in the environment. Data on geology, soils, hypsometry, slope, land use, drainage channels and roads were analyzed in a GIS environment. The erosive processes in BHRSM are inherent to the less consolidated sandy substrate, configuring a natural process. The relief energy for the incision of water flows is meaningful, since the LEF are related to moderate slope in portions of medium altitudes. However, anthropogenic action accelerates erosive processes. It is noteworthy that the increase in the area occupied by crops, doubled in the period of 20 years, configuring a new landscape and dynamics for BHRSM, demanding special attention to this region that tends to intensify the erosivy processes